A review of social values and learning behaviour of student in the district of Satna (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The relationship between social values and learning practices among Satna District pupils is examined in this study. It highlights how early education instills fundamental values like responsibility, equality, service, tolerance, peace, and environmental care. The assessment assesses the influence of the home and school contexts and emphasizes important elements of learning behaviors including motivation, engagement, and study habits. Although there is a high correlation between academic achievement and intrinsic motivation, children' attitudes and learning results are greatly influenced by outside variables such school culture, teaching tactics, and family participation. The study emphasizes how crucial it is to combine learning practices and value education for holistic development, allowing students to grow personally and make valuable contributions to society.